Alterações histológicas e bioquímicas e potencial fisiológico de sementes de soja - Vieira, Bruno Guilherme Torres Licursi [UNESP] (2009)
The soybean seed deterioration has been widely studied during the seed storage. The study was conducted in order to monitor the soybean embryonic tissue and seed deterioration. Soybean seed, cv. MGBR-46 Conquista harvested at three different times: physiological maturity (R7), R7 + 7days and R7 + 15 days and stored in cold room (10 ºC, 45-50% of air RH) and climatic chamber (25 ºC) were used. In the first experiment, in order to obtain information on the structural and physiological damage caused by storage and harvest, the soybean seeds were electromicrographed using an electron microscope scanning and the seed vigor evaluated quarterly using the germination (rolled paper towel and sand as substrate) and vigor (electrical conductivity, tetrazolium, accelerated aging and field seedling emergence) tests. Also the seed water content was determined. In the second experiment, the assessment profiles of the bands of esterase, malate and glutamate dehydrogenase enzymes were also quarterly evaluated. For that, 10 embryonic axes were extracted for each treatment to run electrophoretic analysis. According to the results obtained, it can be concluded that: soybean seeds stored under adverse conditions, in the field after R7 stage and stored at 25 °C for 12 months reduced their physiological potential, damaging the seed coat structure; soybean seeds harvested at different times with high vigor may influence izoenzymatic patterns in response to the storage; the enzyme analyses were sensitive to evaluate the physiological potential, indicating the begin of soybean seed deterioration in function of storage and harvest times; the activity of esterase, malate and glutamate dehydrogenase enzymes may be influenced by time and storage temperatures